Point of Care Ultrasound (POCUS) in Bedside Diagnosis of Pyomyositis - Olusegun Oduyoye; Euan Thomas (CINQUILL Medical Publishers Inc., 2022)
A 43 year old man with a history of IV drug use, and presenting with three days of painful and swollen left calf, was referred to exclude deep vein thrombosis (DVT). Ultrasound showed no evidence of DVT. An area of localised warm, erythematous, which was disproportionately tender, prompted a point of care ultrasound (POCUS) assessment. POCUS confirmed a hypoechoic area in the underlying tissue, likely representing a collection because of no recent trauma. It led to prompt antibiotic therapy for the treatment of his pyomyositis. The patient surgical team reviewed the patient and recommended a conservative approach with a satisfactory clinical outcome that led to a safe discharge. Overall, this case demonstrates the versatility of POCUS as an efficient diagnostic tool in the acute setting, and it also helped to differentiate cellulitis from pyomyositis.